1996
DOI: 10.1021/bi960750e
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Binding Site of Human Brain Hexokinase As Studied by Molecular Modeling and Site-Directed Mutagenesis

Abstract: The interaction of ATP with the active site of hexokinase is unknown since the crystal structure of the hexokinase-ATP complex is unavailable. It was found that the ATP binding site of brain hexokinase is homologous to that of actin, heat shock protein hsc70, and glycerol kinase. On the basis of these similarities, the ATP molecule was positioned in the catalytic domain of human brain hexokinase, which was modeled from the X-ray structure of yeast hexokinase. Site-directed mutagenesis was performed to test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 33 publications
3
36
0
Order By: Relevance
“…In human hexokinase I, electron paramagnetic resonance (50) and modeling (17) suggested that Mg 2ϩ interacts with Asp-532, Arg-539, and Asp-657, which are equivalent to Asp-8, Lys-15, and Asp-95 of StHK, through water molecules. Furthermore, the importance of these residues for activity has been confirmed by mutagenesis (51)(52)(53).…”
Section: Resultsmentioning
confidence: 92%
“…In human hexokinase I, electron paramagnetic resonance (50) and modeling (17) suggested that Mg 2ϩ interacts with Asp-532, Arg-539, and Asp-657, which are equivalent to Asp-8, Lys-15, and Asp-95 of StHK, through water molecules. Furthermore, the importance of these residues for activity has been confirmed by mutagenesis (51)(52)(53).…”
Section: Resultsmentioning
confidence: 92%
“…Asn537 is part of a loop, conserved in sequence between ecGlK (Asn14) and yeast hexokinase (Asn91), and is associated with nucleotide binding. A Thr680Val mutant of hexokinase I showed a decrease in k cat of ϳ2,000-fold, while the Thr680Ser mutant only decreased ϳ2.5-fold, showing the importance of this hydrogen bond in catalysis (74).…”
Section: Resultsmentioning
confidence: 94%
“…3). A combination of modeling (3) and electron paramagnetic resonance studies in solution (48) (74). A hydrated Mg 2ϩ binding site has also been suggested for the P. furiosus ADP-dependent glucokinase (34).…”
Section: Resultsmentioning
confidence: 99%
“…This is close enough to transfer the ␥-phosphate group of ATP to the C6 hydroxyl. In the analysis of human brain hexokinase I, the mutation of Asp532 in its ATP-binding motif, which structurally corresponds to Asp8 of SgGlkA, to Lys or Glu results in a significant loss of the enzymatic activity (57). In the structure of SgGlkA-glucose-AMPPNP, Asp8 locates between AMPPNP and Asn105 and seems to recognize the ␥-phosphate group of ATP.…”
Section: Resultsmentioning
confidence: 99%